Assessing vocabulary size in Malaysian preschoolers: insights from the Malaysian English cross-linguistic lexical task and parents of multilingual children questionnaire - Lew, Joe W.; Łuniewska, Magdalena; Lee, Soon Tat; Yap, Ngee Thai (Routledge, 2025)
This paper introduces the first freely available Malaysian English vocabulary size assessment for 4- to 6-year-old Malaysian children: the newly developed Malaysian English Cross-linguistic Lexical Task (MECLT). Using MECLT scores to measure vocabulary development, the study further explores the efficiency of two approaches: the sum of the number of home languages versus a language exposure composite score, in classifying children’s language profiles (monolingual, bilingual, or multilingual). Sixty children who predominantly speak English at home were assessed on their comprehension and production of nouns and verbs. Significant age effects in MECLT scores were observed between 4- and 5-year-olds, as well as between 4- and 6-year-olds, suggesting that the MECLT is a valuable tool for capturing vocabulary growth among Malaysian preschoolers. Furthermore, in analysing predictors of MECLT scores, the study found that the home language model, which includes age and the number of home languages, was the most accurate predictor of vocabulary size. In contrast, the language exposure composite score model, while detailed, did not significantly enhance predictive accuracy and proved to be more complex and time-consuming.